Introduction to communications technologies a guide for non-engineers - Jones, Stephan S.; Kovac, Ronald J.; Groom, Frank M. (CRC Press, Taylor & Francis Group, 2016)
Used in the core curriculum at Ball State University's graduate professional program in Information and Communication Sciences, this textbook is designed for graduate and undergraduate students who do not necessarily have a high level of technical expertise, but need to have some understanding of the technical functions of information and communication technologies to prepare them for working in a corporate environment